From bribes to international corruption: the Odebrecht case. Issue 3 (25th November 2019) - Morales, Sergio; Morales, Oswaldo
Abstract : Learning outcomes: The contribution of the present case lies in the critical view that every business actor should exercise – be it general manager, middle management, supervisor or executive – when building a strong organizational culture in corrupt political environments. Case overview/synopsis: The purpose of this case study is to explore the dilemma in which Marcelo Odebrecht, once CEO of Odebrecht, found/determined whether to continue with the business model established by the founders of Odebrecht or take a new path for the organization. After exploring the corrupt acts of Odebrecht and the scope of Operation Lava Jato, the reader can reflect on the importance of organizational culture (according to the three levels proposed by Schein) in the face of the emergence of corruption. By generating discussions about organizational culture, business ethics, political culture and corruption, the organizational culture of Odebrecht is problematized in relation to its real behavior. Complexity academic level: Students of administration, business and international business undergraduates and graduates, as well as members of senior management in companies in the infrastructure sector. Also, given the plurality of possible readings, it is recommended that the case also be used in courses or specializations in organizational psychology, organizational sociology or organizational anthropology. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 5: International Business.